EFEKTIVITAS MODUL PEMBELAJARAN INOVATIF UNTUK MENINGKATKAN HASIL BELAJAR PADA PENGAJARAN LAJU REAKSI - Manihar Situmorang (JURNAL PENELITIAN BIDANG PENDIDIKAN, 2014)
The efectivity of innovative learning module to improve students’ achievement on the teaching of chemical rate is explained in this paper. The study is aimed to develop an innovative chemistry learning module for senior high school (SHS) students that can be used as learning edia on the teaching of chemical rate. The research is carried out by integration of laboratory experiments, field activities, and interactive learning media into chemistry topic of chemical rate, followed by standardization of the contents to obtain package of innovative chemistry module. The results showed that developed module is effective to improve student’s achievement in chemistry. Students outcomes in experimental class which are taught with innovative learning module (M=86.27±5.92) was found higher than that in control class (M=76.20±6.35), where both groups are significantly different (ttest 6.55 > ttable 1.319). Chemistry materials in learning module are able to motivate students to study independently. Interactive learning media in electronic module can bring the students become independent learners that facilitates the students moves from teacher centre learning into students centre learning.Keywords: Learning module, Innovative learning, Chemical rate, Learning media.